2012
DOI: 10.1021/bm3001292
|View full text |Cite
|
Sign up to set email alerts
|

Mucin Biopolymers As Broad-Spectrum Antiviral Agents

Abstract: Mucus is a porous biopolymer matrix that coats all wet epithelia in the human body and serves as the first line of defense against many pathogenic bacteria and viruses. However, under certain conditions viruses are able to penetrate this infection barrier, which compromises the protective function of native mucus. Here, we find that isolated porcine gastric mucin polymers, key structural components of native mucus, can protect an underlying cell layer from infection by small viruses such as human papillomaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
161
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(165 citation statements)
references
References 45 publications
2
161
1
1
Order By: Relevance
“…A previous study suggested that during IAV infection, mucin acts as an immobilization substrate for the virus on the cell surface (29). Furthermore, a recent study revealed that increased MUC5AC secretion appears to play a protective role against influenza virus infection (12).…”
Section: Galnt3 Expression Is Associated With Mucin Production and Thmentioning
confidence: 99%
“…A previous study suggested that during IAV infection, mucin acts as an immobilization substrate for the virus on the cell surface (29). Furthermore, a recent study revealed that increased MUC5AC secretion appears to play a protective role against influenza virus infection (12).…”
Section: Galnt3 Expression Is Associated With Mucin Production and Thmentioning
confidence: 99%
“…NHBE cells produce mucus, which is a primary defense against respiratory pathogens and can inhibit influenza virus infection (48)(49)(50). Viral NA proteins are required for mucus degradation, allowing viral attachment to sialylated cellular receptors (50,51).…”
Section: Generation and Genetic Stability Of Recombinant Influenza Bmentioning
confidence: 99%
“…Those mucins can act as an infection shield by trapping various viruses in the biopolymer matrix [ 1 ] and they reduce bacterial adhesion to surfaces. [ 2,3 ] Mucins also form highly hydrated and lubricative layers that protect the underlying epithelium from dehydration and shear stress that emerge during eye blinking or when swallowing food.…”
mentioning
confidence: 99%